2016
DOI: 10.1097/aci.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

Emerging therapeutics for ocular surface disease

Abstract: Recent findings about the pathophysiology of DED and ocular allergy have led to the greater understanding of the molecular and cellular mechanisms of ocular surface diseases leading to the potential novel targets for immunomodulation of anterior surface ocular disorders. New topical glucocorticoids, leukotriene receptor antagonists, IL-1 antagonists, IL-5, IL-4/IL-13 antagonists, integrin antagonists, and quinolone derivatives appear to be encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…A small LFA-1 antagonist called Lifitegrast (SAR 1118) demonstrated in phase III clinical trials to significantly and safely relieve DES symptoms ( 39 ). Lifitegrast acts as an antagonist to LFA-1, resulting in the inhibition of T-cell activation, migration, and proliferation ( 40 ). However, other parameters to assess ocular function, such as Schirmer’s test results, tear breakup time, and inferior corneal staining, did not improve significantly ( 41 ).…”
Section: Current Therapeutic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A small LFA-1 antagonist called Lifitegrast (SAR 1118) demonstrated in phase III clinical trials to significantly and safely relieve DES symptoms ( 39 ). Lifitegrast acts as an antagonist to LFA-1, resulting in the inhibition of T-cell activation, migration, and proliferation ( 40 ). However, other parameters to assess ocular function, such as Schirmer’s test results, tear breakup time, and inferior corneal staining, did not improve significantly ( 41 ).…”
Section: Current Therapeutic Strategiesmentioning
confidence: 99%
“…However, other parameters to assess ocular function, such as Schirmer’s test results, tear breakup time, and inferior corneal staining, did not improve significantly ( 41 ). In July 2016, Xiidra ® was the first United States Food and Drug Administration (US-FDA)-approved LFA-1 agonist for treating DES ( 40 ).…”
Section: Current Therapeutic Strategiesmentioning
confidence: 99%
“…Paradoxically, not only a suppressed immune system but also an overactive immune system can allow a commensal to behave as a pathobiont, resulting in a similar phenotype. While under conditions of immune homeostasis an IL‐17 response is beneficial and protects from pathogens, in models of DED and various forms of keratitis, IL‐17 is highly pathogenic, and its neutralization by antibodies or suppression by corticosteroids or mTOR inhibitors leads to the alleviation of the characteristic symptoms of disease . Data from animal models have suggested that in these diseases adaptive CD4 + T cells are primed against a self or unknown antigen in the draining lymph node to produce IL‐17, migrate to the eye, and cause tissue destruction .…”
Section: Can Ocular Commensals Become Pathobionts?mentioning
confidence: 99%
“…Ocular allergy occurs in 15%–25% of the general population. 1 , 2 In other countries, antigens include grass, 3 differing from those that cause allergic conjunctivitis in Japan. 4 , 5 Japanese cedar pollinosis is a common disease with an age-adjusted estimated prevalence of 19.4% in Japan 4 and is considered to be a national affiction.…”
Section: Introductionmentioning
confidence: 99%